Strategies to enhance health and well-being of dairy calves: exploring the use of prebiotics and environmental enrichment - Velasquez Munoz, Ana, author; Pinedo, Pablo, advisor; Han, Hyungchul, committee member; Callan, Robert, committee member (Colorado State University. Libraries, 2018)
Replacement dairy calves and heifers represent the future for dairy producers. However, rearing healthy animals is not an easy task, since the first day of life calves encounter stressors and management systems that might impact their future health and survival. It is a fundamental production management need to identify and understand these critical windows of stress in the pre-weaned and weaned life in order to create strategies that benefit young animals. This thesis is focused to exploring alternatives for prevention and treatment of neonatal diarrhea and measuring changes in behavior and health when an enriched environment is provided in the first weeks after weaning and grouping in collective pens. In chapter 1, a brief literature review related with health and well-being of dairy calves is presented. The objective of the experiment presented in chapter 2 is to evaluate the addition of stabilized rice bran (SRB) in the milk of neonatal Holstein calves for a period of 28 days and its effects on health, immunity and performance. A paired comparison design was performed with a control (n=45) and a treatment group (n=45). The variables analyzed were neonatal diarrhea presentation, time to recovery from a moderate diarrhea episode, animal removal, concentration of IgA in feces, and average daily gain (ADG). After the treatment period was completed, health, disease presentation, and animal removal was analyzed until weaning through the use of farm records. No differences were found for any of the variables studied in the 28 days of SRB addition or in the follow up until weaning. iii Chapter 3 is focused on the time of weaning, when dairy calves are grouped for the first time in their lives. The objective was to evaluate the effects of an automated grooming brush on health, behavior and performance through a paired comparison design, with one treatment group (n= 81) and one control group (n=81). Four groups of calves were housed in pens of 19 to 22 animals for 3 weeks. One automated brush was placed per treatment pen. Individual behavior data was obtained through the use of 3-D accelerometer sensors. The variables analyzed included disease presentation, time to first clinical disease, animal removal due to disease, and ADG. The 3-D sensor data allowed analysis of "eating", "rumination", "not active", "active", and "high active" behavioral activities, as daily averages and hourly averages. No differences were found for animal removal, time to first clinical disease, or ADG. A tendency was found for the presentation of diseases, indicating that control calves were more likely to be detected sick. Additionally, significant differences were found for "eating" time in favor of treatment calves (P=0.01), and "not active" time in favor of control calves (P=0.014) by day. Hourly differences were found for the variables "eating" time; "not active" time , and "high active" Indicating that treatment calves spent less time "not active" and more time "eating" than control calves by day and more time high active at certain hours than control calves. From our results, the addition of SRB in milk of pre-weaned calves had no an effect on health, immunity or performance of pre-weaned calves. The presence of an automated brush in calves housed in collective pens had a positive effect in the behavior of weaned calves.
Keywords: dairy calves; environmental enrichment; well-being; dairy health; automated brushes; prebiotic